FACTORS AFFECTING STUDENTS INTEREST IN BECOMING PUBLIC ACCOUNTANTS - Lande, Adriani; Irawan , Mohamad Rizal Nur; Syaikhudin, Ahmad Yani (Journal of Economic and Economic Policy, 2024)
This study aims to examine the influence of labor market considerations, financial rewards, and professional risks on accounting students' interest in pursuing a career as public accountants at the Islamic University of Darul Ulum Lamongan and STIE Cendekia Bojonegoro. Methods: The research employed a quantitative associative approach, using a saturated sampling technique, with a sample of 71 final-year accounting students. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS Version 25. Results: The findings reveal that labor market considerations, financial rewards, and professional risks each have a significant positive effect on students' interest in becoming public accountants, with t-test results indicating strong statistical support for all three variables. Simultaneously, these factors collectively influence students' career interests, highlighting their complementary role in shaping aspirations. Novelty: This study underscores the significance of professional risks as a motivating factor, demonstrating that perceived risks, when associated with high potential rewards, can positively influence career decisions. This insight provides a nuanced understanding of the factors driving career preferences among accounting students in Indonesia, with implications for educational institutions and professional organizations aiming to enhance interest in the public accounting profession.